The Dynamics of Educational Services Marketing in the Digital Era - Anis Zohriah; Abdul Mu’in; Sonny Rohimat; Saad Al Faqih (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
Marketing of educational services in the digital era has undergone a fundamental transformation due to shifts in prospective student behavior and increasingly fierce competition. This study aims to comprehensively examine the dynamics of educational services marketing in the digital era, focusing on shifting strategies, the role of social media, and their implications for educational institutions. This research is based on a literature review with a descriptive-qualitative approach. Data were collected through documentation techniques from research articles published since 2023 in accredited scientific journals, which were then analyzed using qualitative content analysis techniques to synthesize the findings. The results show that the unique characteristics of educational services—such as intangibility and variability—demand the adaptation of marketing strategies from traditional to more personalized and data-driven digital models. Marketing is no longer just about promotion but also about building strong relationships with online communities. Social media has proven to be a crucial tool in building a digital brand and reputation through authentic content and proactive interactions. The study concludes that the success of educational institutions in the digital era depends heavily on their ability to holistically integrate digital strategies, manage their online reputation, and prioritize the student experience. Thus, adapting digital marketing is no longer an option but a necessity to ensure the sustainability and relevance of the institution.